Investigation of the Trailing Edge Modification Effect on Compressor Blade Aerodynamics Using SST k-_ Turbulence Model - Mongkol Kaewbumrung; Worapol Tangsopa; Jatuporn Thongsri (My University, 2019)
A gas turbine power plant in Thailand had the problem of compressor blade fracture in Stages 6–8, which was caused by housing damage. This gas turbine has a total of 15 stages. The housing damage reduced the lifetime of blades to an unacceptable level. This article shall report the solution and outcomes. Three-dimensional (3D) compressor blade models in the problematic stages were prepared by a 3D scanning machine to find a solution based on computational fluid dynamics (CFD), and then were completed for simulation by adding Stages 5 and 9 to become a multi-stage axial model. The latter models were modified by trimming the trailing edge by 1-, 5-, and 10-mm. Using ANSYS CFX R19.2 software, the CFD results of the trailing edge modification effect on flow using the shear stress transport (SST) k-ω turbulence model revealed aerodynamics inside the problematic stages both before and after blade modifications. Modifying the blade by 5 mm was suitable, because it had lesser effects on aerodynamic parameters: pressure ratio, drag, and lift coefficients, when compared to the modification of 10 mm. The larger the modification, the greater the effect on aerodynamics. The effects on aerodynamics were intensified when they were modified by 10 mm. The validation of base line blades was conducted for the overall compressor parameters that were compared with the measurable data. These results were accepted and gave positive feedbacks from engineers who practically applied our reports in a real maintenance period of gas turbine.
Keywords: Trailing edge; Leading edge; Turbomachinery Performance and Optimization